Analysis of the operation of a cold thermal energy storage system cooperating with an air conditioning system under temperate climate conditions - Grzebielec, Andrzej; Katana, Katarzyna (International Conference “Environmental Engineering”, 2026)
Increased share of renewable energy sources and the dynamic nature of cooling demand in air-conditioning systems have intensified the need for effective thermal energy storage solutions, particularly under temperate climate conditions, where cooling loads vary significantly between day and night. The aim of this study was to investigate whether the integration of a cold thermal energy storage unit based on sorption technology with an air-conditioning system can improve system operation under variable cooling demand and fluctuating electricity availability. It was hypothesized that sorption-based cold storage can reduce peak electricity demand and enhance the flexibility of air-conditioning systems supplied with renewable energy. The study was conducted using a numerical and operational analysis of an air-conditioning system coupled with a sorption-based cold storage unit. System performance was evaluated under representative temperate climate conditions, considering variable cooling loads, intermittent renewable electricity generation, and time-dependent electricity prices. Key performance indicators included cooling energy cov-erage, storage utilization, and electricity consumption profiles. The results indicate that the application of cold thermal energy storage enables a significant shift in cooling production from daytime peak periods to nighttime or periods of high renewable energy availability. The sorption storage system demonstrated high volumetric energy density, allowing effective cold storage with reduced spatial requirements, and contributed to a measurable reduction in peak electrical power demand. The findings suggest that sorption-based cold thermal energy storage represents a rational and effective solution for improving the operational flexibility and energy efficiency of air-conditioning systems in temperate climates, particularly when integrated with variable renewable energy sources.
Keywords: sorption; thermal storage; cold thermal storage; air conditioning